2019
DOI: 10.14429/dlsj.4.13556
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation and Evaluation of Ricebean (Vigna Umbellata) Extrusion Process for Downstream Food Processability

Abstract: Ricebean(Vigna umbellata), a native bean of North-Eastern part of India has not been explored fully for development of convenience foods although it is loaded with various vitamins, minerals, dietary fiber, phytochemicals and bioactive compounds. The effect of extrusion parameters namely moisture content, barrel temperature and screw speed on expansion ratio, extrudate density, and breaking strength was investigated by using response surface methodology. It was observed that moisture content of flour had signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Lira Filho ( 2002) and Jakkanwar et al (2018) extruding WCF in a single screw also found negative effects of temperature on the SEI, but Marques (2013) obtained a positive correlation. Bepary et al (2019) also found negative effects of temperature when using ricebean (Vigna umbellata (Thunb.) Ohwi & H. Ohashi) flour and a twin screw extruder.…”
Section: Sectional Expansion Index (Sei)mentioning
confidence: 99%
See 2 more Smart Citations
“…Lira Filho ( 2002) and Jakkanwar et al (2018) extruding WCF in a single screw also found negative effects of temperature on the SEI, but Marques (2013) obtained a positive correlation. Bepary et al (2019) also found negative effects of temperature when using ricebean (Vigna umbellata (Thunb.) Ohwi & H. Ohashi) flour and a twin screw extruder.…”
Section: Sectional Expansion Index (Sei)mentioning
confidence: 99%
“…Strauta & Muizniece-Brasava (2016) found harder extrudates as well as higher moisture content. Bepary et al (2019) using the same analytical procedure, and the same independent extrusion variables, but in different ranges, obtained ricebean whole flour extrudates with hardness from 9.61 to 27.95 N, with positive effects of rotation speed and moisture, and negative for temperature.…”
Section: Hardnessmentioning
confidence: 99%
See 1 more Smart Citation